Solving viscid Burgers equation by Adomian decomposition Method (ADM), Regular Pertubation Method (RPM) and Homotopy Perturbation Method (HPM) - BAGAYOGO, Moussa; MINOUNGOU, Youssouf; NEBIE Abdoul Wassiha,; PARE, Youssouf (International Journal of Applied Mathematical Research, 2024)
In this paper the Adomian decomposition Method (ADM), Regular Pertubation Method (RPM) and the Homotopy Perturbation Method (HPM) are used to study Burgers equation. Then we compare the solutions obtained by these three methods.